Efektivitas Terapi Murotal Al-Qur'an Terhadap Tingkat Kecemasan Ibu Bersalin - Maya Herlina, Siskha; Ulya, Yadul; Pricilia Yunika, Regina (STIKES Yarsi Mataram, 2023)
Background: Anxiety is a feeling of fear that is unclear and not supported by the situation. Individuals who feel anxious will feel uncomfortable or afraid, but do not know the reason why this condition occurs. Anxiety has no clear, identifiable stimulus. Murotal therapy can speed up healing and reduce anxiety, listening to the holy verses of the Koran has a significant influence in reducing tension in the reflective nerves. Objective: To determine the effectiveness of Murottal therapy on the level of anxiety of women giving birth. Method: This type of research uses quasi-experimental research. The sample in this study was 30 mothers in the first stage of labor. This research uses a one group pretest posttest design approach. Results: Based on the frequency distribution of the effectiveness of murottal therapy on maternal anxiety levels before delivery, it shows that in the intervention group the average anxiety score was 18.28, the lowest anxiety score was 14 and the highest was 23, while in the control group the average anxiety score was 24. .13, the lowest anxiety score is 18 and the highest is 27. Conclusion: Based on the research results, murottal therapy on maternal anxiety levels before giving birth is effective. Suggestion: Murottal therapy has good effectiveness, it is hoped that this therapy can relieve and be a solution to the anxiety experienced by mothers during pregnancy, childbirth and postpartum.